Dukungan Keluarga Pada Ibu Menjelang Menopause - Enur Nurhayati Muchsin Muchsin; Fanda Yulvania (STIKes Payung Negeri Pekanbaru, 2023)
ABSTRACT Family support is the support that individuals receive from people in the family environment such as husbands, children, and parents, so that individuals feel cared for, valued, and loved. Support can serve as a preventive strategy to reduce stress. The purpose of the study was to determine family support for mothers approaching menopause in Bendo Kidul Hamlet, Bendo Village, Pare District, Kediri Regency The research design used was descriptive with a population of 65 people and a sample of 58 people. The sampling technique used was purposive sampling. The research time is from 4 to 9 January 2021.The research instrument uses a questionnaire, the research variable is family support for the mother before menopause. Data analysis uses percentages and quantitative data interpretation. The results obtained from 58 respondents, most of the respondents have good support for as many as 40 respondents (69%). Almost half of the respondents have sufficient support as many as 17 respondents (29.3) and a small proportion of respondents have less support as much as 1 respondent (1.7%). Factors that can influence include age, education level, status in the family, occupation, never getting information, media information. It is hoped that the family will provide support to the mother before menopause, so that the mother can go through the premenopause period well. Keywords: Family Support, Mothers Approaching Menopause.